2019
DOI: 10.4491/eer.2018.306
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of mechanical properties of bio-concrete using Enterococcus faecalis and Bacillus cereus

Abstract: The present study aimed to investigate the potential of Enterococcus faecalis (E. faecalis) and Bacillus cereus (B. cereus) in improving the properties of bio-concrete. E. faecalis and B. cereus strains were obtained from fresh urine and an acid mire water at cell concentration of 1.16×10 12 and 1.3×10 12 cells mL-1 , respectively. The bacterial strains were inoculated in a liquid medium into the concrete with 1, 3 and 5% as replacement of water cement ratio (w/c). The ability of E. faecalis and B. cereus cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…So, a repairing coating of calcium carbonate can behave as a natural calcite skin on the surface of bio-concrete (Achal et al, 2013). The observed reduction of water permeability in bio-concrete specimens reflects the action of the bacterial consortium representing a solution to one of the main problems concerning concrete durability (Alshalif et al, 2019). our results in agreement with several reports ( Luo et al, 2015;Tziviloglou et al, 2016;Balam et al 2017;Choi Sun-Gyu et al, 2017;Shashank and Nagaraja, 2021).…”
Section: Permeabilitysupporting
confidence: 91%
See 1 more Smart Citation
“…So, a repairing coating of calcium carbonate can behave as a natural calcite skin on the surface of bio-concrete (Achal et al, 2013). The observed reduction of water permeability in bio-concrete specimens reflects the action of the bacterial consortium representing a solution to one of the main problems concerning concrete durability (Alshalif et al, 2019). our results in agreement with several reports ( Luo et al, 2015;Tziviloglou et al, 2016;Balam et al 2017;Choi Sun-Gyu et al, 2017;Shashank and Nagaraja, 2021).…”
Section: Permeabilitysupporting
confidence: 91%
“…The surfaces of untreated concrete seemed to be amorphous, without obvious CaCO3 crystals appearance. In contrast, bio-concrete samples demonstrated crystalline surfaces where distinct CaCO3 crystals may recognize (Krishnapriya et al, 2015;Siddique et al, 2016;Alshalif et al, 2019). Reda et al, (2020) were reported that Bacillus flexus is the most potent one amongst the bacterial isolates that can form biofilm.…”
Section: Visual Observation Of Self-healingmentioning
confidence: 99%
“…Therefore, the surface of bioconcrete may have a healing layer of calcium carbonate that functions as a natural calcite skin [49]. As a response to one of the primary issues with concrete durability, the bacterial consortium's activity is reflected in the bio-concrete specimens' observed decrease in water permeability [50]. Several papers [51][52][53][54][55] concur with our findings.…”
Section: Absorption Of Water Test (Sorpativity Test)supporting
confidence: 84%
“…According to Rafat Siddique (2011), bacteria concentration is one of the most critical factors affecting the performance and compressive strength of bio-concrete [ 16 ]. While increasing the bacteria concentration increases compressive strength, exceeding the optimum value can have a negative effect [ 17 ].…”
Section: Introductionmentioning
confidence: 99%